Strong circularly polarized luminescence of an octahedral chromium(iii) complex. Issue 87 (14th October 2019) - Dee, Carolin; Zinna, Francesco; Kitzmann, Winald R.; Pescitelli, Gennaro; Heinze, Katja; Di Bari, Lorenzo; Seitz, Michael
Abstract : The chiral spin–flip luminophore [Cr(ddpd)2 ] 3+ can be resolved into enantiopure material by chiral HPLC. The pure enantiomers display strong CPL activity for the corresponding near-IR phosphorescence. Abstract : The chiral spin–flip luminophore [Cr(ddpd)2 ] 3+ can be resolved into enantiopure material by chiral HPLC. The corresponding enantiomers show very high luminescence dissymmetry factors of up to ∣ g lum ∣≈ 0.093 in circularly polarized luminescence (CPL) measurements for the "ruby-like" phosphorescence transition 2 E/ 2 T1 → 4 A2 in the near-IR region around λ ≈ 775 nm.